E-Learning Adoption in Higher Education Institutions During the COVID-19 Pandemic: A Multigroup Analysis - Shams, Muhammad Shahid; Niazi, Murtaza Masud; Gul, Habib; Mei, Tang Swee; Khan, Kaleem Ullah (Frontiers in Education, 2022)
After the outbreak of novel coronavirus (COVID-19) in late December 2019, in an attempt to mitigate its development, the decision to close institutions around the world was made. To continue imparting education and delivering the learning material to their students, many institutions adopted for digital or E-learning. To support those institutions attempting to digitize their learning during this pandemic, the main aim of this study is to examine the students’ accessibility to and success of E-learning portals. Using the DeLone and McLean (D&M) Model, the study explains the differences between female and male students’ accessibility to E-learning portals. This study compares female and male student groups regarding the usage of the E-learning portal in the higher education context. Using an online google survey, the data were collected from 254 students, including males and females. The study utilized PLS-SEM to perform a multi-group analysis examining female and male student groups. The study found a significant and direct relationship of e-service quality with system use and user satisfaction for females and male student groups. System quality also supported the relationship with user satisfaction. The study further revealed a significant and positive relationship between system use and user satisfaction with E-learning portal success for females and male student groups. This study also concluded that insignificant difference exists in using the E-learning portal between female and male student in higher education institutions.